You didn't give us the equation, but circle equations are in the form;
(x-h)^2 + (y-k)^2 =r^2 where h and k are the x and y coordinate of the center and r is the radius of the circle squared.
You get them either thrift or wrong
Lets count...
3a...thats 1 term
3ab...thats 2
7b....thats 3
-2c....movin on up to 4
-4d....and we end at 5
so this expression has 5 terms since none of the terms can be combined :)
Answer:
![y= -2+\frac{2}{3}x](https://tex.z-dn.net/?f=y%3D%20-2%2B%5Cfrac%7B2%7D%7B3%7Dx)
Step-by-step explanation:
Multiply both sides by 2
2x=3y+6
Move variable to the left-hand side and change its sing
-3y=6-2x
Divide both sides of the equation by -3
![y= -2+\frac{2}{3}x](https://tex.z-dn.net/?f=y%3D%20-2%2B%5Cfrac%7B2%7D%7B3%7Dx)
Answer:
i cant see the image?
Step-by-step explanation:
if someone can please tell me what is shows